Effects of Control Type and Panel Angle on Kitchen Appliance Usability: A Comparative Study of Knob and Touchscreen Panels - Son, Minseok; An, Sehee; Beck, Donghyun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This study empirically examined whether panel angle effects on kitchen appliance control panel usability vary by control type. Two representative types—cooker knobs and touchscreen panels—were tested at four angles (0°, 30°, 60°, 90°), reflecting common configurations in commercial ranges. Usability was assessed through visibility, physical comfort, and preference. Twenty participants performed heat-level adjustment tasks at each angle and rated all measures. Results showed: (1) significant interaction effects between control type and panel angle across all criteria, and (2) substantial main effects of panel angle on evaluation scores. Knob panels achieved higher ratings at steeper angles, while touchscreen panels performed better at flatter angles. These findings provide ergonomic guidance for designing control interfaces that integrate both knobs and touchscreens. Proper panel angle design can enhance visual accessibility, reduce bodily strain, and help prevent musculoskeletal disorders during prolonged and repetitive use.